CHILD POVERTY IN SUMATRA IN 2017 AND 2019: THE MULTIDIMENSIONAL OVERLAPPING DEPRIVATION ANALYSIS (MODA) APPROACH - Atqa, Iffah; Azwardi, Azwardi; Sukanto, Sukanto (Journal of Economic Development, Environment and People, 2021)
Introduction. Poverty is more multidimensional, but monetary-based method measures are merely one-dimensional. The multidimensional approach is more reliable for describing and analyzing children poverty. This study only focused on ten provinces in Sumatra out of 34 provinces in Indonesia. There are five major dimensions of indicators which are housing, facilities, food and nutrition, education, child protection and health. Purposes. This study used Multidimensional Overlapping Deprivation Analysis (MODA) Approach on Alkire-Foster Method as a measuring tool for analyzing children poverty in Sumatra in 2017 and 2019. Results The number of 0-4 year-old-deprived children is decreasing for most dimensions in 2019, compared to 2017, except child protection dimension and the number of 5-17 years-old-deprived children is decreasing for most dimensions, except health dimension. 2) The condition of Child Multidimensional Poverty Index (MPI) becomes better in 2019. 3) Education is the most contributed dimension to child multi-dimensional poverty in Sumatra for 2017, while health dimension for 2019. 4) North Sumatra is the first highest score of Child MPI, headcount ratio, and intensity of poverty. 5) Bengkulu and Lampung are the provinces in 2017 and 2019 experiencing both monetary poverty and child multidimensional poverty above the Indonesia’s poverty rate and Child MPI in Sumatra.